Kontekstualisering as voorvereiste vir profetiese prediking in ’n post-apartheidkonteks - Brits, HJ; Swanepoel, HJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2009)
Contextualising as a prerequisite for prophetical preaching in a post-apartheid context Prophetical preaching as a type of preaching has the character of practical Word application for the distressed. Prophetical preaching carries a message of comfort, encouragement and hope for the “hopeless”. This article argues that a prophetical preacher within a “post-apartheid” South Africa, has to understand the negative discourse that exists within the context of the distressed. This context has to be interpreted and transformed into a positive narrative through the medium of prophetical preaching. Profetiese eskatologie konsentreer op God se verlossing wat nog op hierdie aarde en in hierdie geskiedenis plaasvind (Du Rand, 2007:21).